A rare case of Capnocytophaga canimorsus associated with pneumoperitoneum as a result of gastric ulcer perforation. (January 2022) - Eskell, Matthew; Khan, Hashim
Highlights: Dog bites, scratches and general exposure transmit Capnocytophaga canimorsus. Clinicians need to screen for dog bites and scratches in unknown infections. Capnocytophaga canimorsus rarely occurs in immunocompetent individuals. This is the first case of pneumoperitoneum in a Capnocytophaga canimorsus infection. Abstract: Background: Capnocytophaga canimorsus infections are a rare consequence of dog or cat bites, scratches or general exposure. Their non-specific presenting features and the technical difficulties culturing the bacterium render it a challenging diagnosis. Case report: This case report describes a case of Capnocytophaga canimorsus, in an apparently immunocompetent 58-year-old male, secondary to multiple dog bites and scratches. Following antibiotic therapy, surgical repair of his perforated gastric ulcer and a post-operative stay complicated by delirium he was discharged having made a complete recovery. Results: Literature recognises embolic secondary to Capnocytophaga canimorsus infections however, to the best knowledge of the authors, this is the only reported case of pneumoperitoneum secondary to stress ulceration in a Capnocytophaga canimorsus septicaemia. In this case the identification of multiple dog bites and scratches only occurred retrospectively after Capnocytophaga canimorsus had been cultured. This indicates that these risk factors are not routinely screened for and highlights the importance of identifying such risk when attempting to delineate the cause of sepsis of unknown origin. Conclusion: Whilst being the first case report of pneumoperitoneum secondary to a Capnocytophaga canimorsus infections, this case reports highlights its non-specific presenting features thus the importance of identifying animals bites and scratches when attempting to identify an infection of unknown origin.